Efeito do envelhecimento e do estresse crônico sobre a reação do tecido conjuntivo subcutâneo: estudo histológico em ratos - Rezende, Maria Cristina Rosifini Alves [UNESP]; Kusuda, Ricardo; Marinho, Márcio Von Dreiffus [UNESP]; Felipini, Renata Callestini [UNESP]; Okamoto, Roberta [UNESP]; Okamoto, Tetuo [UNESP]; Alves-Rezende, Luís Guilherme Rosifini; Garcia-da-Silva, Tales Candido [UNESP]; Alves-Claro, Ana Paula Rosifini (My University, 2010)
Physiological functions undergo a gradual retardation that begins around 25-30 years and extends to the death. Moreover, this change affects most severely the activities more complex and more intricate responses to tensions or stress. The purpose of this study was to evaluate histologically in aged rats the effect of chronic stress on the reaction of subcutaneous connective tissue. The purpose of this study was to evaluate histologically in aged rats the effect of chronic stress on the reaction of subcutaneous connective tissue. For this purpose, 60 rats were divided into four groups (GI (control), GII (stressed), GIII (elderly) and GIV (aged / stressed) received dorsal subcutaneous implants of polyethylene tubes containing saline solution. In groups of four animals were sacrificed at 7,14 and 28 days postoperatively. The results allowed to observe more intense inflammatory reaction and tissue organization later in the aged animals subjected to stress.

As funções fisiológicas sofrem um retardo gradual que se inicia por volta de 25-30 anos e se estende até a morte. Além disso, esta alteração afeta mais gravemente as atividades mais complexas e as respostas mais intrincadas às tensões ou estresse. O propósito deste trabalho foi estudar histologicamente em ratos idosos o efeito do estresse crônico sobre a reação do tecido conjuntivo subcutâneo. Para tanto, 60 ratos, divididos em quatro grupos (GI (controle), GII (estressado), GIII (idoso) e GIV (Idoso/Estressado) receberam implante subcutâneo, bilateral e dorsal, de tubos de polietileno contendo soro fisiológico. Em grupos de cinco, os animais foram sacrificados aos 7,14 e 28 dias pós-operatórios. Os resultados obtidos permitiram observar reação inflamatória mais intensa e organização do tecido conjuntivo mais tardia nos animais idosos submetidos ao estresse.
Effect of aging and chronic stress on the reaction of subcutaneous connective tissue: histological study in rats
Keywords: Wound healing; Aged; Hypothalamohypophyseal system; Pituitary-adrenal system; Cicatrização de feridas; Idoso; Sistema hipotálamo-hipofisário; Sistema hipófise-supra-renal